El secreto de la señora - Gamarra, Hugo; Casco Pane, Luis; Ríos, Edda de los; Pardo de Carugati, Dirma (Ara Films Producciones : Centro de Comunicación Audiovisual, 1989)
Two young girls of humble status are hired as maids in a mansion, where an extravagant and despotic lady lives who educates them. Everything changes with the arrival of a strange man in the house. Initiated and shot during the last months of the dictatorship of General Alfredo Stroessner, it was conceived as an allegation against the corruption, perversion and totalitarianism that dominated the country. Like the original story, the script was inspired by real cases recorded by the international press. --